Mechanistic analysis of enhanced methane production during anaerobic digestion of coal by different exogenous microbial consortia - Hongyu Guo; Haodong He; Shufeng Zhao; Xiao Zhou; Man Wang; Zhaoying Chen; Daping Xia (Journal of Environmental Chemical Engineering, 2026)

Seismic behavior of rock slopes containing a partially mobilized sliding surface via centrifuge shaking table testing: Unraveling interaction between seismic load transfer and structural deterioration - Shiyu Li; Shengwen Qi; Bowen Zheng; Songfeng Guo; Guangming Luo; Daping Tai; Jianxian He; Xiaolin Huang (Engineering Geology, 2026)

Ga-N4 single-atom sites as an electronic bridge and nano-anchor for synergistically enhancing PtCo intermetallic electrocatalysts - Zhihao Wang; Zibo Chen; Xiaodong Ji; Yunfa Si; Cheng Chen; HuiHui Jin; Daping He (Chemical Engineering Journal, 2026)

Towards sustainable potato production in China: Optimizing nitrogen and water management with 5R strategies - Zhaolong Pan; Rong Jiang; Daijia Fan; Daping Song; Hanyou Xie; Xiya Wang; Wei Zhou; Ping He; Wentian He (European Journal of Agronomy, 2026)

Vascular Organoids Derived from Capillary malformation-induced Pluripotent Stem Cells Exhibit Disease-Relevant Phenotypes - Vi Nguyen; Anna Harper; Mackenzie Azuero; Isabella Castellanos; Siwuxie He; Marcelo L. Hochman; Camilla F. Wenceslau; Dong-bao Chen; Anil G. Jegga; Yunguan Wang; Daping Fan; J. Stuart Nelson; et al. (Stem Cell Reviews and Reports, 2026)
Capillary malformation (CM) is a congenital vascular anomaly that affects the skin, mucosa, eye, and brain. A major obstacle to mechanistic and drug screening studies for CM has been the lack of preclinical models. In this study, we established vascular organoids (VOs) generated through the self-assembly of vascular lineages of endothelial cells and smooth muscle cells differentiated from CM-induced pluripotent stem cells (iPSC). Within these VOs induced endothelial cells and smooth muscle cells organized into juxtapositions to form vascular branches. CM patient iPSC-derived VOs showed a higher density of endothelial and smooth muscle cell populations and greater vascular branch lengths as compared with VOs derived from iPSCs generated from healthy skin biopsies. Overall, this study represents the first disease-relevant VO model of CM, providing a valuable platform for future mechanistic studies and drug screening.

Scalable electrode substrates for environmentally stable and flexible humidity sensors - Zhenyu Gong; Zibo Chen; Fangzheng Xi; Bo Liu; Yunfa Si; Jie Wen; Xiaodong Ji; Mingyang Tanwei; Cheng Chen; Peng Li; Shaowen Cao; Geng Wu; et al. (Chemical Engineering Journal, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Transparent and lightweight electromagnetic shielding film with resistance to harsh conditions through interpenetrating encapsulation of silver nanowires network - Zhen Huang; Yitong Xin; Jiulin Shen; Lan Shen; Junfeng Liu; Xiping Zeng; Huan Ling; Guoli Tu; Hui Yang; Daping He; Bin Hu (Chemical Engineering Journal, 2025)

Interleukin-9 promotes EMT-mediated PM2.5-induced pulmonary fibrosis by activating the STAT3 pathway - Yuxuan Li; Yi Zhong; Chenwen Li; Zhixia Han; Yan Cui; Renjiang He; Yingyi Liu; Qinlin Cui; Daping He; Zhengquan Hu; Qingbi Zhang; Jun Bai (Archives of Toxicology, 2024)

Thermally-stable and flame-retardant metal-organic framework-based separator for high-performance lithium-ion batteries - Wen Ren; Jiang Liang; Meng Huang; Wei Qian; Ming Zhao; Fan Qiao; Lianmeng Cui; Zixin Zhang; Junjun Wang; Cheng Zhou; Zhe Wang; Qinyou An; et al. (Chemical Engineering Journal, 2024)

Delineating cathodic extracellular electron transfer pathways in microbial electrosynthesis: Modulation of polarized potential and Pt@C addition - Yue Wang; Siyang Yu; Xue Zheng; Xiaobing Wu; Ying Pu; Gaoying Wu; Na Chu; Xiaohong He; Daping Li; Raymond Jianxiong Zeng; Yong Jiang (Bioresource Technology, 2024)

Global impact of enhanced-efficiency fertilizers on vegetable productivity and reactive nitrogen losses - Zhaolong Pan; Ping He; Daijia Fan; Rong Jiang; Daping Song; Lei Song; Wei Zhou; Wentian He (Science of The Total Environment, 2024)

Construction of robust Cu-N4-Pt bond connecting Cu single atoms support and Pt for augmented electrocatalytic process - Huihui Jin; Bingshuai Liu; Pengxia Ji; Zhengying Li; Daping He (Chemical Engineering Journal, 2024)

Effect of excitation frequency and joint density on the dynamic amplification effect of slope surface on jointed rock slopes - Daping Tai; Shengwen Qi; Bowen Zheng; Guangming Luo; Jianxian He; Songfeng Guo; Yu Zou; Zan Wang (Engineering Geology, 2024)

Modelling adaptation measures to improve maize production and reduce soil N2O emissions under climate change in Northeast China - Daijia Fan; Daping Song; Rong Jiang; Ping He; Yaoyao Shi; Zhaolong Pan; Guoyuan Zou; Wentian He (Atmospheric Environment, 2024)

Improving potato productivity and mitigating nitrogen losses using enhanced-efficiency fertilizers: A global meta-analysis - Zhaolong Pan; Daijia Fan; Rong Jiang; Naeem Abbasi; Daping Song; Guoyuan Zou; Dan Wei; Ping He; Wentian He (Agriculture, Ecosystems & Environment, 2023)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.